Metabolic profiling of charged metabolites in association with menopausal status in Japanese community-dwelling midlife women: Tsuruoka Metabolomic Cohort Study. (January 2022) - Watanabe, Keiko; Iida, Miho; Harada, Sei; Kato, Suzuka; Kuwabara, Kazuyo; Kurihara, Ayako; Takeuchi, Ayano; Sugiyama, Daisuke; Okamura, Tomonori; Suzuki, Asako; Amano, Kaori; Hirayama, Akiyoshi; et al.
Highlights: Evidence suggest that amino acids play key roles in obesity-related diseases. Few studies have focused on amino acids and related metabolites in the specific context of menopause. The association between menopausal status and charged metabolites was explored in over 1000 midlife women. Multiple charged metabolites were associated with menopausal status. Amongst the differentially expressed metabolites were those relevant to atherosclerosis. Abstract: Background: Emerging evidence has shown that charged metabolites, such as amino acids, may play an important role in the pathogenesis of various metabolic disorders, many of which women in the postmenopausal period are at high risk of developing. This study examined the metabolic profile of middle-aged Japanese women to investigate alterations in charged metabolites induced by menopausal transition. Methods: The participants were 1193 female residents aged 40–60 at the baseline survey of the Tsuruoka Metabolomics Cohort Study. We investigated the cross-sectional association of menopausal status with 94 metabolomic biomarkers assayed in fasting plasma samples via capillary electrophoresis time-of-flight mass spectrometry using linear regression analysis. Results: Among the participants, 529 were premenopausal, 132 were in menopausal transition (MT), and 532 were postmenopausal. Significant differences were found in age, blood pressure, glucose and lipid levels, and smoking and drinking habits among the three groups. The concentrations of 5 metabolites in the MT group and 15 metabolites in the postmenopausal group were significantly higher than those in the premenopausal group after adjusting for confounding factors. When classified into pathways, these metabolites were related to the tricarboxylic cycle, urea cycle, and homocysteine metabolism, some of which are linked to arteriosclerosis. Conclusion: Multiple charged metabolites were associated with women's menopausal status, showing a gradual increase as women shifted from pre-, to peri-, to postmenopause. These findings might reflect the early changes behind the increased risk of dyslipidemia, diabetes, cardiovascular disease, and osteoporosis in later life.